Real-World Use of Molnupiravir in the Treatment of Outpatients with SARS-CoV-2 Infection-A Patient Profile Based on the Experience of a Tertiary Infectious Disease Center - Anca Streinu-Cercel; Victor Daniel Miron; Alina Alexandra Oană; Mădălina Irimia; Ramona Ștefania Popescu; Ioana Andreea Dărămuș; Maria Magdalena Moțoi; Gabriela Jana Ceapraga; Oana Săndulescu (MDPI AG, 2022)
During the current pandemic, the gap between fundamental research and clinical practice has been narrowing at a faster pace than ever before. While clinical trials play the main role of confirming the safety and efficacy of new drugs, a drug's introduction into clinical practice creates the need for further research in order to best position the use of the novel drug in terms of when, to whom, and how it would be best administered to achieve the best possible outcome under feasible clinical circumstances. We briefly present the results of a retrospective analysis of the characteristics of outpatients treated with molnupiravir in a tertiary care infectious disease hospital in Bucharest, Romania, between February and March 2022, when Romania was experiencing its fifth wave of COVID-19. A total of 46 outpatients received molnupiravir treatment and had complete clinical data available; of them, 56.5% (n = 20) were males and the median age was 48.5 years (IQR: 37.8, 67.0 years). A total of 54.2% (n = 26) of patients had at least one chronic condition. Of the 45 patients who underwent lung CT imaging evaluation, 13 (28.9%) showed changes suggestive of COVID-19 pneumonia. COVID-19 vaccination status was strongly protective for pneumonia (p = 0.002). All patients were symptomatic, and molnupiravir was initiated at a mean time from onset of symptoms of 3.5 (±1.5) days. At phone follow-up 5 days after the initial evaluation and initiation of molnupiravir treatment, all patients, except for one, confirmed a favorable course under treatment, with no worsening of COVID-19 severity and improvement in symptoms; none of them progressed to respiratory failure or required hospitalization. In conclusion, treatment was well tolerated and associated a favorable outcome of COVID-19 in routine practice in a clinical population that was slightly older and had a smaller burden of comorbidities and a higher rate of COVID-19 vaccination compared to that from the pivotal trial.